2014
DOI: 10.1111/jace.13219
|View full text |Cite
|
Sign up to set email alerts
|

Novel Glass‐Ceramic Composition as Sealant for SOFCs

Abstract: This work deals with the design, the characterization, and testing of a novel glass-ceramic to be used as sealant for planar solid oxide fuel cells and its compatibility with Mn1.5Co1.5O4-coated Crofer22APU. Thermal, sintering, and crystallization behavior and thermo mechanical properties of the sealant are reviewed and discussed, indicating therefore that these compositions can be deposited at 850C and provide an excellent compatibility with both the Mn1.5Co1.5O4-coated Crofer22APU and the anode-supported ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The interface between the glass-ceramic sealant and the Mn 1.5 Co 1.5 O 4 spinel coating on Crofer22APU was found to be free of cracks; this is mainly due to a good thermal expansion coefficient match of the glass ceramic sealant (10.8 Â 10 À6 C À1 ) [28] with that of Mn 1.5 Co 1.5 O 4 spinel (10.8 Â 10 À6 C À1 ) [37]. The interface between the Crofer22APU and the Mn 1.5 Co 1.5 O 4 coating was also found to be continuous; the Mn 1.5 Co 1.5 O 4 sintered layer showed complete adherence to the Crofer22APU surface and no spalling was observed on cooling after sintering.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The interface between the glass-ceramic sealant and the Mn 1.5 Co 1.5 O 4 spinel coating on Crofer22APU was found to be free of cracks; this is mainly due to a good thermal expansion coefficient match of the glass ceramic sealant (10.8 Â 10 À6 C À1 ) [28] with that of Mn 1.5 Co 1.5 O 4 spinel (10.8 Â 10 À6 C À1 ) [37]. The interface between the Crofer22APU and the Mn 1.5 Co 1.5 O 4 coating was also found to be continuous; the Mn 1.5 Co 1.5 O 4 sintered layer showed complete adherence to the Crofer22APU surface and no spalling was observed on cooling after sintering.…”
Section: Resultsmentioning
confidence: 97%
“…A new SiO 2 -based glass ceramic sealant [28] was subsequently deposited on MneCo oxide coated Crofer22APU (previously heat treated at the optimized sintering temperature of 1000 C for 2 h in air). The glass sealant was deposited from an ethanol-based slurry (particle size below 38 mm) and then heated in a tubular furnace at 850 C for 30 min in Ar at the heating rate of 5 C min À1 to obtain a dense glass ceramic sealant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of formation of sodium chromate is a concern and as result other groups have so far not considered the use of sodium in diopside systems. However, when working on alternative glassceramic systems, the present authors [11,14] previously showed that such problems may be overcome by tailor-making compositions where sodium was able to diffuse away from the sealant-interconnect interface and thus prevent any undesirable effects.…”
mentioning
confidence: 91%
“…The use of metallic brazes could provide a possible bonding solution, however, these can be expensive and have been reported to be unable to survive in the dual atmosphere present of the device [5,7]. Among the candidate sealants, glasses and glass-ceramics are likely to be the materials of preference as they exhibit better resistance to the severe service environment (oxidizing and reducing) than brazing alloys [8][9][10][11][12][13][14]. On the other hand compressive seals like mica-based seals can result in high leakage levels and it may be necessary to use them in combination with brazes or glass (for example infiltrating the glass into mica papers) [3,15].…”
mentioning
confidence: 99%